Epidemiology of Legionella in environments for recreational, tourism or physical activities (Italian Journal of Public Health, 2004)
Legionella is a waterborne microorganism responsible of severe pneumonia. Legionnaire’s disease and Pontiac fever are clinical syndromes related to contaminated environments.Outbreak sources have been identified in sport facilities, thermal springs, spas, hotels, campsites, cruise ships and other structures for recreational or tourism purposes. Infection spreads by inhalation of contaminated aerosols from showers or whirlpool baths. Exposure to properly maintained swimming pools does not represent a major risk factor. Several prevention strategies and decontamination procedures are available.